2017
DOI: 10.2147/jpr.s125693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decompression on behavioral, electrophysiologic, and histomorphologic recovery in a chronic sciatic nerve compression model of streptozotocin-induced diabetic rats

Abstract: PurposeTo determine susceptibility to decompression surgery in diabetic and nondiabetic peripheral neuropathy using a chronic compression neuropathy model.Materials and methodsTwenty-four streptozotocin-induced diabetic rats were randomly divided into three groups: group I, chronic compression of the left sciatic nerve for 4 weeks with decompression; group II, similar without decompression; and group III, sham exposing the sciatic nerve only. The other 24 nondiabetic rats were assigned to groups IV–VI, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The pathogenesis of diabetic neuropathy is complex. Hyperglycemia leads to an excess of intramitochondrial reactive oxygen species, inflammatory reactions, and edema formation in peripheral nerves (21). The double crush hypothesis states that a diabetic nerve is more susceptible to compression than a nondiabetic nerve (7).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of diabetic neuropathy is complex. Hyperglycemia leads to an excess of intramitochondrial reactive oxygen species, inflammatory reactions, and edema formation in peripheral nerves (21). The double crush hypothesis states that a diabetic nerve is more susceptible to compression than a nondiabetic nerve (7).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the cell bodies of motor neurons are located in the anterior horn of the spinal cord. The blood–neuron interface is less well-protected in the dorsal root ganglion than in the spinal cord [ 20 , 21 , 22 ]. It is noteworthy to point out that surgical decompression can be an effective treatment for diabetic neuropathy [ 23 ].…”
Section: The Mechanisms Of Diabetic Neuropathies Are Complexmentioning
confidence: 99%
“…5,6 Several studies have reported nerve decompression animal models, established using methods such as removal of ligations after chronic constriction injury (CCI) surgery or removal of silicone that was wrapped around nerves. [7][8][9][10] These studies reported that DS ameliorates mechanical and thermal hypersensitivity. However, despite DS being the gold standard treatment for chronic nerve compression injuries in clinical settings, the molecular mechanisms underlying its effectiveness are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Decompression surgery (DS) is the standard treatment used to relieve the symptoms of such injuries when conservative treatments are ineffective 5,6 . Several studies have reported nerve decompression animal models, established using methods such as removal of ligations after chronic constriction injury (CCI) surgery or removal of silicone that was wrapped around nerves 7–10 . These studies reported that DS ameliorates mechanical and thermal hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%